PENGENALAN LATIHAN KEKUATAN OTOT UNTUK KEBUGARAN JASMANI DI JAKARTA BARAT - Setiadi , Tjie Haming; Pandean, Felicia; Haryanto , Yonathan Julian (Jurnal Serina Abdimas, 2023)
ABSTRACT Most urban people spend most of their time working, studying, doing household chores and playing gadgets. Someone doesn't realize how important it is to train muscles. The FK UNTAR dedication team conducted health education aimed at introducing muscle strength training techniques that can be done at home Educational activities related to muscle strength training were carried out on 17 and 18 May 2023 by 25 participants. There were more female participants than male participants and the age of the participants was in the range of 20-56 years. Participants who complained of frequent pain in the knee as many as 13 participants and 14 participants did not exercise routinely. Health education related to muscle strength and endurance is given to partners in the form of understanding the benefits of muscle strength training and exercises that can be done at home. The education participants felt helped because they were introduced to this type of muscle strength training and felt that it needed to be done regularly at home. Muscle strength training educational activities need to be carried out continuously in order to assess the benefits of muscle strength training. ABSTRAK Masyarakat perkotaan sebagian besar sebagian besar waktunya dipergunakan bekerja, belajar, mengerjakan pekerjaan rumah tangga serta bermain gadget, Seseorang tidak menyadari pentingnya melatih otot. Tim pengabdian FK UNTAR melakukan edukasi kesehatan bertujuan mengenalkan tehnik latihan kekuatan otot yang dapat dilakukan di rumah Kegiatan edukasi terkait latihan kekuatan otot telah dilakukan tanggal 17 dan 18 Mei 2023 dihadiri oleh 25 peserta. Peserta wanita lebih banyak dibandingkan peserta laki-laki dan usia peserta berada pada rentang 20-56 tahun. Peserta yang mengeluh sering merasa nyeri pada bagian lutut sebanyak 13 peserta dan 14 peserta tidak rutin latihan otot. Edukasi kesehatan terkait kekuatan dan ketahanan otot yang diberikan kepada mitra berupa pengertian manfaat latihan kekuatan otot serta latihan yang dapat dilakukan di rumah. Peserta edukasi merasa terbantu karena diperkenalkan jenis latihan kekuatan otot dan merasa perlu dilakukan tertur di rumah. Kegiatan edukasi latihan kekuatan otot perlu dilakukan secara kontinu agar menilai manfaat dari latihan kekuatan otot.